Comparative study of total prostate specific antigen and free to total prostate specific antigen ratio in the diagnosis of prostate cancer - Chakraborty, L; Ahmed, AN; Paul, BK; Haque, A; Ara, A; Nabi, S; Nessa, M (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):98-102 The abstract of this article is available on the PubMed website